Re-Creation of Linguistic Features in GermanLanguage Literary Translations. - Khomidov Navruz Uzbek Ramadanovich (Zien Journals, 2022)
This article discusses the re-creation of linguistic characteristics in Germanlanguage art translations.
Keywords: Tarjima; characteristics; education; industry